Dinamika Psikologi Komunikasi Digital dalam Membangun Pengendalian Diri Mahasiswa Gen Z - Supeno; Diana Elfiyatul Afifah (Bahasa Indonesia, 2024)
This study aims to analyze the dynamics of digital communication psychology in shaping the self-control of Gen Z students and the mechanism of fear of missing out (FOMO) on social media. The study uses a phenomenological qualitative approach with subjects aged 18–23 years who actively use social media. Data were collected through in-depth interviews, observation of digital habits, and documentation, then analyzed thematically. The results of the study show that FOMO is formed through a cycle of stimulus–meaning–response: digital notifications and posts trigger interpretations based on affiliation needs, giving rise to anxious emotions, which then encourage compulsive behavior that is reinforced by platform algorithms. FOMO affects three dimensions of self-control, namely attention and priority disruption at the cognitive level, social anxiety at the emotional level, and impulsivity and task procrastination at the behavioral level. Students develop multidimensional coping strategies including technical restrictions on device use, cognitive reframing of content meaning, strengthening face-to-face relationships, and spiritual practices. These findings confirm that self-control in the digital age is not solely a personal capacity, but rather the result of a negotiation between individual agency and the structure of communication technology. The research implies the importance of digital communication psychology literacy in higher education to strengthen students' emotional regulation and attention management. This study contributes to enriching communication psychology studies by offering a conceptual model of FOMO based on the process of meaning-making and contextual self-control practices among Indonesian students.